Structure of a hexameric RNA packaging motor in a viral polymerase complex. - Huiskonen, J; Jäälinoja, H; Briggs, J; Fuller, S; Butcher, S (2007)
Packaging of the Cystovirus varphi8 genome into the polymerase complex is catalysed by the hexameric P4 packaging motor. The motor is located at the fivefold vertices of the icosahedrally symmetric polymerase complex, and the symmetry mismatch between them may be critical for function. We have developed a novel image-processing approach for the analysis of symmetry-mismatched structures and applied it to cryo-electron microscopy images of P4 bound to the polymerase complex. This approach allowed us to solve the three-dimensional structure of the P4 in situ to 15-A resolution. The C-terminal face of P4 was observed to interact with the polymerase complex, supporting the current view on RNA translocation. We suggest that the symmetry mismatch between the two components may facilitate the ring opening required for RNA loading prior to its translocation.